SISTEM INFORMASI PENJUALAN PADA DISTRO SATRIANI NEW STORE BERBASIS WEB - Josua Aprilio Putra (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2023)
Distro Satriani is a shop that sells t-shirts, jackets, bags, etc. which is located on Jl. Hasanudin No. 2A, Terbono, Selosari, Kec. Magetan, Magetan Regency. The sales, marketing and promotion system used today is still using a manual system. It is very necessary to facilitate service for customers who are far from out of town. To realize an application by conducting research that aims to help Distro Satriani in expanding the scope of promotions, helping customers who come from outside the city to keep shopping and maximize product sales. So it was built an online sales system on web-based Satriani distribution using the PHP programming language and MySQL database. By using the waterfall research method. As well as testing is done using Blackbox Testing to check whether the system that has been created is in accordance with the business processes running in the company and can overcome existing problems. Based on the results of system testing, the Sales Information System at Distro Satriani can handle the sales process effectively. In addition, this system can display sales-related reports easily and quickly